Pattern recognition in bioinformatics 6th IAPR International Conference, PRIB 2011, Delft, The Netherlands, November 2-4, 2011 : proceedings - Loog, Marco; SpringerLink (Online service). (Heidelberg New York Springer, 2011)
This book constitutes the refereed proceedings of the 6th International Conference on Pattern Recognition in Bioinformatics, PRIB 2011, held in Delft, The Netherlands, in November 2011. The 29 revised full papers presented were carefully reviewed and selected from 35 submissions. The papers cover the wide range of possible applications of bioinformatics in pattern recognition: novel algorithms to handle traditional pattern recognition problems such as (bi)clustering, classification and feature selection; applications of (novel) pattern recognition techniques to infer and analyze biological networks and studies on specific problems such as biological image analysis and the relation between sequence and structure. They are organized in the following topical sections: clustering, biomarker selection and classification, network inference and analysis, image analysis, and sequence, structure, and interactions.
Electronic reproduction.
Keywords: Bioinformatics -- Congresses; Pattern recognition systems -- Congresses; Computational biology -- Methods -- Congresses; Biological markers -- Congresses; Pattern recognition, Automated -- Methods -- Congresses; Electronic books